Genetic engineering : manipulating the mechanisms of life - Hodge, Russ , 1961- (Facts On File, 2009)
Examines the fields of modern molecular biology from their beginning to recent discoveries and technical breakthroughs. Focuses on cell theory, cloning, ethics of genetic engineering, and the history of genetic engineering to the science of heredity.